The Effect Of Capital Structure, Leverage And Liquidity On Eraning Quality (Studies in Property and Real Estate Companies Listed on the Indonesian Stock Exchange Period 2018-2022) - Fatimatuh Zahro; Preatmi Nurastuti (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
Earnings quality is a measure of how well the company's financial performance is reflected in the financial statements. The purpose of this study was to determine the effect of capital structure, leverage, and liquidity on earnings quality. The population of this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. The sample of this study obtained 65 samples with purposive sampling technique. This analysis method uses Multiple Linear Regression with SPSS 29 software. This study concludes that capital structure has an effect on earnings quality. while leverage has no effect on earnings quality. likewise with liquidity has no effect on earnings quality. Keywords: Capital Stucture, Earning Quality, Leverage, Liquidity